The Influence of E-Servqual and Brand Image on Loyalty Mediated by BPJS Customer Trust in Malang Raya - Utami, Ngesti Wahyuningtyas; Astuti, Widji; Supriadi, Bambang (Journal of Management Economic and Financial, 2025)
The existence of BPJS makes healthcare services affordable for the community in Indonesia. Nationally, more than 95% of BPJS participants indicate that the public has confidence in BPJS, which supports the formation of loyalty. JKN participants in Malang Raya reach > 90% of the total population, but there are still inactive independent participants >20%. This situation demands that BPJS be able to maintain the sustainability of the JKN program, which can ensure the continuity of health financing. As an appropriate effort, it is to increase the loyalty of independent participants. The type of this research is Explanatory Research that analyzes the influence of E-Servqual and brand image on loyalty mediated by trust in Malang Raya. The population in this study consists of 618,893 JKN PBPU participants in the Malang Raya area, with a sample size of 200 participants. Data were obtained using a questionnaire and the Google Form application. The descriptive research results show that 100% of respondents agree that E-Servqual, brand image, and trust contribute to loyalty. The hypothesis test of the direct influence of E-Servqual on loyalty proved to be insignificant, but brand image has a significantly positive effect on loyalty. In the indirect influence of E-Servqual on loyalty, mediated by trust, it was proven to be significantly positive, whereas the indirect influence of brand image on loyalty, mediated by trust, was not significant. The results indicate that JKN participants have received services as expected through electronic services (E-Servqual), the image of the BPJS organization is perceived as good and of high quality, thus respondents trust and remain active BPJS participants. Based on the discussion, it is recommended that BPJS increase attention to the issues experienced by JKN participants through the website, as well as respond to participant complaints and periodically evaluate the website.